Araça amarelo: atividade antioxidante, composição nutricional e aplicação em barra de cereais - Vanin, Camila da Rosa (2015)
Brazil has a great diversity of native fruits, which are not always widely consumed, being sold only in certain regions, due to their difficulty of post-harvest conservation. One such fruit is yellow guava, interesting source of nutrients. To promote the consumption and use of this fruit to the consumer public in different regions of the country, this study evaluated the incorporation of yellow Ya-cy araçá in formulating a cereal bar. Therefore, fruits were evaluated for their chemical, physical and chemical characteristics and bioactive compounds in different stages of maturation yellow guava (green, mature and dried forms). The behavior of guava yellow front of to UV-C radiation was also evaluated. After these reviews, there was obtained yellow ripe guava flour after previous tests, was added to the base formulation cereal bar. For the experimental planning and development of the formulations was used factorial design 22 with a central point. The developed formulations were subjected to sensory evaluation using for treatment of multivariate data analysis (Principal Component Analysis- ACP). The preferred formulation in sensory evaluation was evaluated in their physical characteristics (texture), physical-chemical (moisture, ash, lipids, proteins, carbohydrates, dietary fiber and calorie), mineral content and fatty acid profile. The results indicated that the added yellow guava cereal bar developed in this study is one way to application and use of guava, increasing the consumption of fruit to different regions of the country, and can be considered a functional product, not only to contain the fruit in its composition, but also to present many beneficial nutrients that contribute to the health of consumers.